Thermochemical processes principles and models - Alcock, C. B. (Oxford ; Boston : Butterworth-Heinemann, 2001)
Today the study of materials is concerned with the underlying thermodynamic and chemical processes involved in the manufacture and processing of a wide range of materials - metals, ceramics, semi-conductors, plastics and composites. For the first time, this book provides a quantitative description and examples of the application of physical chemical concepts to the processing and degradation of metallic and other inorganic materials, from the atomic scale to the analysis of industrial processes. Thermochemical Processes: Principles and Models deals with processes dominated in turn by the gas phase (such as chemical vapour deposition), the solid phase (such as powder metallurgy electroceramics and high-temperature corrosion) and the liquid phase (such as extraction metallurgy and glass-making). C.B. Alcock provides information which will prove invaluable to academics and workers involved in high temperature industries and in particular to those with an interest in the scientific analysis of processes - which will be most useful to those working in the field of modelling. First ever quantitative approach to the subject of Thermochemical processing. Companion volume to Kubachewski et al.
Introduction; Vapour deposition; Chemical vapour deposition; Gaseous reactions, Photochemical Reactions; Molecular decomposition; Adsorption and surface energies of metals; Catalysis of Metals; Solid State Kinetics; Charge and heat transport properties; Structure and diffusion properties of metals; Diffusion in non-metallic systems; Solid state processes in oxides; Gas-solid reactions; Processes involving liquids; Extraction Metallurgy; Appendices; Bibliography; Index.
Includes bibliographical references and index.
Keywords: Thermodynamics; Chemical processes; Materials at high temperatures; Electronic books